Land Use Change Pattern of Change and Strategy Directions for Spatial Utilization Control in Bogor Regency - Nur Irfan Asyari; Santun R. P Sitorus; Arif Wicaksono (Riviera Publishing, 2024)
The designation of Bogor Regency as a National Activity Center encourages regional development, a very high population leads to rapid development and uncontrolled land use change. Therefore, spatial modeling based on land change prediction is needed that can be used as a basis for directing spatial utilization control policies. The purpose of this research is to know and analyze the pattern of land use change and analyze the direction of spatial use control strategies in Bogor Regency. The research was conducted in Bogor Regency. The analysis used ArcGIS 10.8 Overlay and IDRISI Selva Edition and ISM v. 2.3. The results of the analysis of land use change in between 1997 and 2010, 87.98% of land use remained unchanged, while 12.01% changed. From 2010 to 2023, 73.16% remained unchanged, and 26.84% changed. The predominant land change pattern was from Dry Land Agriculture to Dry Land Agriculture-Rice Fields, while the least common was Open Land to Dry Land Agriculture and back to Open Land. By 2036, expected increases include settlements, shrubs, and Open Land, with decreases anticipated in dryland agriculture, forests, and paddy fields. The alignment of land use with the RTRW spatial plan shows 58.68% aligned, 23.85% transitional, and 17.46% misaligned. It is recommended to maintain land use aligned with the spatial plan, utilize transitional areas, and revise the RTRW for areas that are permanently misaligned. Strategies to control spatial utilization include enhancing technical training, improving infrastructure, aligning staff with organizational needs, and refining spatial planning policies and dispute resolution.